22 In vivo evaluation of ethanol extract of forsythia suspensa (thunb.) vahl (fruit) in anti-inflammatory and analgesic activities. (5th December 2017) - Wang, JM; Cui, Y; Chen, SQ; XB, Li; Feng, WS; Cai, H; Chen, RX
Abstract : Objectives: The dried fruit of Forsythia suspensa (Thunb.) Vahl (FSTV) is a typical heat-clearing and detoxicating herb according to traditional Chinese medicine theory. This study was undertaken to evaluate the anti-inflammatory and analgesic activities of 85% ethanol extract of FSTV (FSTV-ET) in vivo. Methods: Conventional reflux extraction method was used to prepare FSTV-ET with a yield of 42.7%. The analgesic activity of FSTV-ET was evaluated using the hot plate test and acetic acid-induced abdominal writhing test, and the anti-inflammatory activity was evaluated by the xylene-induced ear oedema model in female Kunming (KM) mice. Lipid peroxidation product malondialdehyde (MDA) and inflammatory mediator prostaglandin (PG) E2 were both detected using methods reported in the literature. Results: FSTV-ET exerted analgesic activity with a significant dose-dependent increase in latency in the hot plate test. The percentage inhibition suggested that FSTV-ET exhibited analgesic activity in the central nervous system. Meanwhile, FSTV-ET at 0.16, 0.32, and 0.64 g/kg strongly inhibited the acetic acid-induced writhing response. FSTV-ET also exerted analgesic activity in the peripheral nervous system. Moreover, FSTV-ET demonstrated a significant anti-inflammatory effect against xylene-induced oedema in a dose-dependent manner, and reduced MDA and PGE2 levels. Conclusions: These findings indicate that FSTV-ET can produce anti-inflammatory and analgesic activities in vivo, and the mechanism is likely to be related to inhibiting lipid peroxidation and inflammation. Acknowledgements: Supported by project grants from the National Natural Science Foundation of China (Grant No. 81503269), the Funding Scheme for Young Key Teachers of Colleges and Universities in Henan Province (Grant No. 2014GGJS-072), and the Science and Technology Project of Zhengzhou (Grant No. 20150309).